Preliminary assessment of the emission levels of ammonia and hydrogen sulfide in different production modalities in poultry farms in Costa Rica - Herrera, Jorge (2013)
A characterization of the ammonia and hydrogen sulfide emissions generated by different production models in poultry farms of Costa Rica was carried out. It was found that egg production farms have the largest emissions since they mostly use management systems based on cages with pits which generates a high emission of ammonia (16 ppm). While the fattening farms had the lower emissions since they mostly use open systems, which are low ammonia emission models (6 ppm). There were no significant concentrations of hydrogen sulfide in the evaluated models, except when a mechanical removal of mounds of chicken manure, with several weeks of storage, took place. A peak of 163 ppm of hydrogen sulfide was observed during the process. The ammonia emissions were modeled for some farms using an atmospheric dispersion model, AERMOD (USEPA), to determine the impact in the surroundings. Using the results of the validated model, it was found that the ammonia concentrations around the farms met the local regulation for air quality. But in some cases is highly probable to exceed the odor threshold for ammonia, which is one of the main complaints of the population living around this kind of agricultural and livestock activities.